A taxonomic revision of the genus Diplonevra Lioy (Diptera: Phoridae) from China - Liu, Guang-Chun; Yang, Meng (Zootaxa, 2016)
The Chinese species of Diplonevra are revised, with 16 recognised species from both the Oriental and Palaearctic parts of China. The following 8 species are described as new to science: D. corniculata sp. nov., D. trapezia sp. nov., D. vecticrassa sp. nov., D. lamella sp. nov., D. furcavectis sp. nov., D. brevicula sp. nov., D. triangulata sp. nov., D. spinibotra sp. nov. All known species are re-identified, re-described and illustrated. Diagnostic characters of the base of the posterior face of the hind trochanter and femur are depicted in detail. A revised identification key to Chinese species based on males is presented.